A proposed disaster preparedness plan for the University of the Philippines College of Music Library - Delos Reyes, Maria Sherlie B.; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
Every library boasts of a special collection of materials which sets them apart from others. Hence, a sound and viable Disaster Preparedness Plan is a must to ensure that the collection remains safe and protected in the event iof a disaster. This study focused on building a simple and direct disaster preparedness plan to ensure the safety of the unique collection of the College of Music Library. Through the employment of descriptive research, the researcher was able to come up with a disaster preparedness plan to get the institution started towards a more secure future of their collection. The researcher made use of a risk assessment checklist and a survey questionnaire to obtain information from all four library staff of the College of Music Library. Some of the findings are: 1) the library has four staff, one head librarian, an assistant librarian and two library aides; 2) the most common disaster that occurs is typhoon and flooding; 3) the library staff has high awareness of the possibility of a disaster occurring and 4) the library in its years if i.e. [of] existence has not been hit by any major disaster. Toward the last part of this research, the researcher presents a disaster preparedness plan for the institution based on the information gathered in the checklist and survey questionnaire.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) College of Music Library; Emergency management -- Phiiippines -- Quezon City